Comparison of the Concept of Justice in Islamic Law and Western Law - Karimullah, Suud Sarim (UNISKA LAW REVIEW, 2023)
This study describes an in-depth analysis of the concept of justice in Islamic law and Western law by relying on literature studies involving comparative and integrative literature analysis. This approach was chosen to obtain comprehensive results in the comparative understanding of the concept of justice in Islamic law and Western law. The study results stated that justice in Islamic law has deep roots in religious teachings and is often closely related to religious values. In contrast, Western law tends to be more secular based on legal principles that arise from historical developments and philosophical thought. In comparison, there are similarities in the humanitarian principles underlying the laws of War, Peace, human rights, and individual protection. However, differences in legal sources, basic principles, and implementation create different frameworks for achieving justice. In an age of increasingly connected globalization, this better understanding of differences and similarities can potentially promote cross-cultural dialogue, international cooperation, and joint efforts in achieving justice and peace worldwide.